Performance comparison between RGB and HSV color segmentations for road signs detection - Mohd Ali, Nursabillilah; Mohd Mustafah, Yasir; Alang Md Rashid, Nahrul Khair (Trans Tech Publications Ltd., Switzerland, 2013)
This paper compares the performance of RGB and HSV color segmentations method in road signs detection. The road signs images are taken under various illumination changes, partial occlusion and rotational changes. The proposed algorithms using both RGB and HSV color space are able to detect the 3 standard types of colored images namely Red, Yellow and Blue. The experiment shows that the HSV color algorithm achieved better detection accuracy compared to RGB color space.